Characterising the molecular basis of WDR82 binding in multiple contexts - Kelley, JR (2022)
Precise regulation of gene expression is essential for the development of multicellular organisms. The progression of RNAPII transcription through initiation, elongation and termination is accompanied by mRNA processing events such as capping and splicing, and requires numerous regulatory factors. The extended C-terminal domain (CTD) of the largest RNAPII subunit, RBP1, consists of YSPTSPS heptapeptide repeats that can be post-translationally modified in a number of ways, most notably by phosphorylation. These different phosphorylation states occur in distinctive patterns across genes and have been implicated in regulating various aspects of transcription and mRNA processing. WDR82 is a small WD40-repeat protein which has been shown to bind the RNAPII CTD when it is phosphorylated on serine 5 (S5P), a modification associated with transcription initiation. Removal of WDR82 from cells has profound effects on transcription genome-wide. However, interpreting these results is complicated by the inclusion of WDR82 in three independent complexes that regulate transcription in different ways; the SET1 complexes act at promoters to support gene transcription, the PNUTS-PP1 complex promotes cleavage and polyadenylation-coupled transcription termination, and the ZC3H4 complex mediates premature transcription termination. Whilst the subunit compositions of these complexes have been characterised to varying extents, the molecular basis of WDR82 incorporation into each complex is unknown. Furthermore, the molecular function of WDR82 in these different contexts has not been well characterised. It has been proposed that WDR82 mediates SET1A and ZC3H4 binding to S5P CTD, whilst its role in the PNUTS complex is less clear.